The Impact of Inflation Rate, Leverage, and Firm Size on Banking Financial Performance - Isnawan, Delfihanna Permata; Supratiwi, Wiwik (Electronic Journal of Education, Social Economics and Technology, 2026)
This study examines the effect of inflation, leverage, and firm size on the financial performance of the banking sector. The research employs a quantitative approach using secondary data obtained from the annual financial statements of banks listed on the Indonesia Stock Exchange. The sample consists of 258 observations analyzed through multiple linear regression using SPSS software. The findings indicate that the inflation rate does not have a significant effect on financial performance. Leverage has a negative and significant effect, meaning that higher levels of debt tend to reduce bank performance. Meanwhile, firm size has a positive and significant effect on financial performance, suggesting that banks with larger asset scales tend to achieve better performance. The novelty of this study lies in the integration of agency theory and signaling theory to simultaneously explain the influence of macroeconomic factors and internal firm characteristics on banking financial performance during the post-pandemic recovery period of 2019–2024. These findings imply that internal factors, such as capital structure and firm scale, play a more substantial role in influencing bank performance compared to macroeconomic factors such as inflation.